(untitled) (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
"PhoneWars" is a two-dimensional party game which contains 9 mini-games that can be played by two to four players using their smartphone as the controller. This game was created using Unity for PC or laptop and the controller is created for Android. Easy Wifi Controller was used as the asset to connect the controller to the game. Photoshop was used to design the characters and other sprites for the game. Each mini-game have different gameplay and theme. Players have to collect points by competing in mini-games. Testing was done using blackbox testing, alpha testing, and beta testing with a questionnaire distributed to 75 respondents divided into 31 groups. The results show that the game "PhoneWars" is a multiplayer game that has a pretty good graphics, easy to play, and features a smartphone as a controller that makes it easier for players to play this game.